Sensitive and visual identification of Chlamydia trachomatis using multiple cross displacement amplification integrated with a gold nanoparticle-based lateral flow biosensor for point-of-care use - Chen, Xu; Yuan, Wei; Zhou, Qingxue; Tan, Yan; Wang, Ronghua; Dong, Shilei (Frontiers in Cellular and Infection Microbiology, 2022)
Chlamydia trachomatis is the leading cause of bacterial sexually transmitted infection (STI) and remains a major public health challenge, especially in less-developed regions. Establishing a rapid, inexpensive, and easy-to-interpret point-of-care (POC) testing system for C. trachomatis could be critical for its treatment and limiting further transmission. Here, we devised a novel approach termed a multiple cross displacement amplification integrated with gold nanoparticle-based lateral flow biosensor (MCDA-AuNPs-LFB) for the highly specific, sensitive, user-friendly, and rapid identification of C. trachomatis in clinical samples. A suite of MCDA primers based on the C. trachomatis ompA gene from 14 serological variants (serovar A-K, L1, L2, and L3) were successfully designed and used to establish the assay. Optimal assay conditions were identified at 67°C, and the detection procedure, including nucleic acid preparation (approximately 5 min), MCDA amplification (30 min), and AuNPs-LFB visual readout (within 2 min), was completed within 40 min. The all-in cost for each test was approximately $5.5 USD. The limit of detection (LoD) was 10 copies/reaction, and no cross-reaction was observed with non-C. trachomatis microbes. A total of 135 suspected C. trachomatis-infection genital secretion samples were collected and simultaneously detected using real-time quantitative PCR (qPCR) in our assay. Compared with the qPCR technology, the MCDA-AuNPs-LFB sensitivity, specificity, positive predictive value, and negative predictive value were 100%, 96.20%, 94.92%, and 100%, respectively. Hence, our MCDA-AuNP-LFB assay exhibited considerable potential for POC testing and could be used to identify C. trachomatis in clinical settings, particularly in low-income regions.